The Effect of Direct Financial Compensation, Job Performance Appraisal and Physical Work Environment on Employee Job Satisfaction - Erina Rulianti; Giri Nurpribadi; Febrianti Awaliyah (PT Mattawang Mediatama Solution, 2024)
Job satisfaction is defined as a positive emotional state from a person's work experience about what job they deserve in return. The purpose of this study was to determine the effect of direct financial compensation, performance appraisal, and the physical work environment on job satisfaction of PT. J Ekstrim Tech Indonesia. The type of research used is quantitative. With a simple random sampling technique (Simple Random Sampling). Based on the research population at PT. J Ekstrim Tech Indonesia is a total of 130 employees. The sample in this study were 98 respondents who were calculated using the slovin formula. Data collection using the method of observation, questionnaires, literature and interviews. The data analysis method used in this study is quantitative data analysis using the SPSS For Windows program. After the data is collected, data analysis is carried out by grouping data based on the variables studied, performing calculations to answer the problem formulation and performing calculations to test the hypothesis. Data analysis was performed with multiple linear regression. The results showed that direct financial compensation partially had a positive and significant effect on employee job satisfaction, performance appraisal partially had a positive and significant effect on employee job satisfaction, the physical work environment had a partial positive and significant effect on employee job satisfaction. Based on the results of the simultaneous test of direct financial compensation variables, performance appraisal and the physical work environment simultaneously influence employee job satisfaction.